Culturally sensitive design: transforming mediklinik al waleed into a community- centric healthcare heaven in Sungai Limau, Yan, Kedah / Ts. Normaziana Hassan ... [et al.] - Hassan, Normaziana; Yusoff, Zaidi; Md Shahid, Shuhaila; Juhari, Muhammad Amin; Shafie, Muhammad Amer (Universiti Teknologi MARA, Kedah, 2024)
The importance of clinic design in fostering patient comfort is undeniable. Nevertheless, many existing designs fail to provide a truly comforting experience due to impracticality, lack of ergonomics, and outdated aesthetics. Evidence-based design, as advocated by Lawson (2010), underscores the significance of improving healthcare architecture. Meanwhile, Uldrich (1984) emphasized the role of buildings in promoting healing through evidence-based design decisions. Against this backdrop, this paper proposes a new private clinic identity and image in rural Sungai Limau, Yan, Kedah. Collaborating with design experts, a refreshed design concept was crafted, integrating interior and exterior elements to establish a unique identity that resonates with the local community. Materials and design elements were meticulously selected, focusing on ergonomics, lighting, and workspace functionality. Consequently, the proposed Islamic-inspired design caters to physical comfort and addresses psychological elements to welcome patients from diverse backgrounds. The transformation of Mediklinik Al Waleed aims to provide a welcoming and comfortable environment for rural communities seeking healthcare services. By infusing tranquility into the clinic's ambiance, the design endeavors to elevate the overall patient experience and establish a recognizable brand within the community. Notably, the proposed design covers all clinic areas comprehensively, ensuring a cohesive and inviting space for patients. Contextual relevance, cultural significance, and community engagement are paramount in the design process and aligning the clinic with the specific needs and values of Sungai Limau. Balancing tradition with modernity, the design integrates Islamic architectural elements with contemporary medical facilities, creating a holistic healthcare space that serves as a community hub. In conclusion, by embracing culturally sensitive design principles and prioritizing community needs, Mediklinik Al Waleed seeks to become a cornerstone of healthcare in Sungai Limau. This collaborative effort between healthcare providers and design experts aims to enhance the well-being and prosperity of the rural community, setting a new standard for healthcare premises in the region.